‘Very brief advice’ (VBA) on smoking in family practice: a qualitative evaluation of the tobacco user’s perspective - Papadakis, Sophia; Anastasaki, Marilena; Papadakaki, Maria; Antonopoulou, Μaria; Chliveros, Constantine; Daskalaki, Chrissi; Varthalis, Dionisis; Triantafyllou, Sofia; Vasilaki, Irene; McEwen, Andy; Lionis, Christos (Université d'Ottawa | University of Ottawa, 2020)
Abstract Background Very Brief Advice on smoking (VBA) is an evidence-based intervention designed to increase quit attempts among patients who smoke. VBA has been widely disseminated in general practice settings in the United Kingdom, however its transferability to Southern European settings is not well established. This study sought to document the perspectives of Greek general practice patients in terms of the acceptability and satisfaction with receiving VBA from their general practitioner (GP) and its influence on patients’ motivation to make a quit attempt. We also examine patient identified barriers and facilitators to acting on VBA. Methods Semi-structured interviews were conducted with 50 patients who reported current tobacco use recruited from five general practices in Crete, Greece. All patients received VBA from their GP and interviews were conducted immediately after the GP appointment. Thematic analysis was used to analyze data. Results The majority of patients were satisfied with the VBA intervention. Approximately one quarter of patients reported they were motivated to make an attempt to quit smoking after receiving VBA from their GP. Patients identified a clear preference for VBA to be delivered in a supportive manner, which communicated genuine concern versus fear-based approaches. Patients with an existing smoking-related illness were more likely to report plans to act on their GP’s VBA. Patients not ready to quit smoking indicated they would be likely to seek the support of their GP for future quit attempts as a result of VBA. Many patients reported low self-efficacy with quitting and apprehension about available quit smoking supports. Conclusions VBA was positively received by the majority of smokers interviewed. Participating patients confirmed the motivational role of advice when delivered in a supportive and caring manner. Personal health status, beliefs about quit smoking supports, and low self-efficacy appear to influence patient’s motivation to make an aided quit attempt.